Pedagogi Identitas Keagamaan: Official Knowledge dan Interkulturalisme Pendidikan Islam di Papua - Idrus al Hamid (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This article discusses two education concepts from sociological point of view, namely official knowledge as the product of critical pedagogy experts and the concept of intercultural education that is pinned to solve the problem of identity in educational environment. This article makes Jayapura a case example where the two concepts can be implemented both theoretically and practically. With a phenomenological approach in the field, this study found that the concept of "Official Knowledge" which was often framed as resistance to government power could be shifted to an "acceptance attitude" to resolve conflicting identity conflicts in society. The condition is that the state must have power to regulate the knowledge and awareness of the facts of diversity in Indonesia. The intercultural approach can derive diversity through education that promotes interaction, communication, and the formation of an attitude of mutual understanding and acceptance between one individual and another, between social reality and knowledge in educational institutions, and between different religious groups.